Impact of Right Ventricular Function on Mortality and Reoperation Rates in Cardiovascular Surgery - Erol Sener; Mete Hıdıroğlu; Murat Yücel; Hüseyin Ünsal Erçelik; Kemal Erdoğan; Emrah Uğuz; Muhammet Fethi Sağlam (Sakarya Tıp Dergisi)
Objective: This study aimed to investigate the impact of preoperative right ventricular (RV) function on postoperative outcomes such as mortality, reoperation rates, valve size, and other clinical variables in patients undergoing tricuspid valve surgery. Methods: This retrospective study included 100 patients who underwent tricuspid valve surgery. Patients were categorized into four groups based on preoperative RV function: normal, mildly depressed, moderately depressed, and severely depressed. RV function was assessed using echocardiographic parameters, including tricuspid annular plane systolic excursion (TAPSE), tissue Doppler imaging (TDI), mean pulmonary artery pressure (MPAB), and valve size. Postoperative outcomes, including mortality and reoperation rates, were analyzed. Results: Patients with severely depressed RV function had significantly higher mortality rates (p=0.035). Reoperation rates also increased as RV function worsened (p=0.006). No significant difference was found between groups regarding valve size (p>0.05) or the type of surgery (sternotomy or thoracotomy) (p=0.714). Conclusion: Right ventricular dysfunction significantly increases postoperative mortality and reoperation rates in patients undergoing tricuspid valve surgery. Careful preoperative evaluation of RV function, including valve size, is critical for improving surgical outcomes.